The impact of vitamin E supplementation on sperm analysis in varicocelectomy patients: a triple-blind randomized controlled trial - Kasra Saeedian; Saeed Davaryar; Maryam Emadzadeh; Alireza Akhavan Rezayat (Trials)
Abstract Objective To evaluate the impact of vitamin E supplementation on sperm analysis results in patients post-varicocelectomy. Martials and method This single-center, triple-blind, randomized controlled trial was conducted at Imam Reza Hospital, Mashhad, Iran. Ninety male patients, aged 15–25 years, with infertility and varicocele grade 2 or 3, were randomized into two groups. The intervention group received 400 units of vitamin E daily for 3 months, while the control group received a placebo. Sperm analysis was conducted before and 3 months after the intervention. Statistical analyses were performed using SPSS version 23, with significance set at P < 0.05. Results A total of 90 patients were enrolled and equally randomized into two groups (n = 45 per group). The mean age was 30.68 ± 6.31 years. Post-intervention, the improvement in sperm motility was significantly higher in the vitamin E group compared to the placebo group (P = 0.03). Both groups showed significant improvements in sperm motility, count, and morphology from pre- to post-intervention (P < 0.001). Conclusion Vitamin E supplementation post-varicocelectomy is associated with improved sperm parameters, suggesting potential benefits in the management of male infertility related to varicocele. However, varicocelectomy alone also results in significant improvements. Trial registration This study is registered at the Iranian Registry of Clinical Trials (IRCT20200911048689N1). Registered on October 10, 2020.